Experiential learning as preparation for leadership: An exploration of the cognitive and physiological processes. Issue 4 (5th June 2017) - Waller, Lee; Reitz, Megan; Poole, Eve; Riddell, Patricia M.; Muir, Angela
Abstract : Purpose: The purpose of this paper is to explore whether challenging experiences on development programmes would simulate leadership challenges and therefore stimulate the body's autonomic nervous system response. The authors also aimed to determine whether increase in autonomic arousal would be related to learning, and/or moderated by personality variables. Design/methodology/approach: The research used heart rate (HR) monitors to measure HR continuously over a two-day simulated learning experience. This was used to calculate autonomic arousal which was taken to be the difference between resting HR measured during sleep and HR during critical incidents (CIs) (HR). The authors correlated this with self-reports of learning immediately after, and one month after, the programme to assess the impact of autonomic arousal on perceived learning, as well as with variety of psychometric measures. Findings: The research found significant correlations between (HR) during CIs and perceived learning which were not related to personality type. The research also found a significant correlation between (HR) and learning during a control event for individuals with "approach" personalities. Research limitations/implications: Whilst a significant result was found, the sample size of 28 was small. The research also did not empirically assess the valence or intensity of the emotions experienced, and used only a self-report measure of learning. Future research should replicate the findings with a larger sample size, attempt to measure these emotional dimensions, as well as obtain perceptions of learning from direct reports and line managers. Practical implications: The findings from the research help clarify the mechanisms involved in the effectiveness of experiential learning, and contribute to the understanding of the influence of personality type on perceived learning from experiential methodologies. Such understanding has implications for business schools and learning and development professionals, suggesting that development experiences that challenge leaders are likely to result in learning that is longer lasting. Originality/value: The research extends the literature regarding the value of learning through experience, the role of autonomic arousal on learning, and the impact of negative emotions on cognition. The research makes a unique contribution by exploring the impact of experience on arousal and learning in a simulated learning experience and over time, by demonstrating that simulated experiences induce emotional and physiological responses, and that these experiences are associated with increased learning.